Actinidiaceae endémicas del Perú - Young, Kenneth R. (2006)
The Actinidiaceae are represented in Peru by one genus, Saurauia, and 11 species (Brako & Zarucchi, 1993), mostly shrubs. Here we recognize three endemic species, all found in forests of the Very Humid Montane Forest region, between 1800 and 3000 m elevation. Only one endemic species has been registered to date within Peru’s protected areas system.